Capoeta anamisensis, a new species from the Minab and Hasan Langhi River drainages in Iran (Teleostei: Cyprinidae) - Zareian, Halimeh; Esmaeili, Hamid Reza; Freyhof, Jörg (Zootaxa, 2016)
Capoeta anamisensis, from the Minab and Hasal Langhi River drainages in southern Iran, belongs to the C. trutta species group. Capoeta anamisensis is distinguished from other species of the C. trutta species group by the combination of the following characters: flank silvery without black spots; 56–67 scales in total along the lateral series; 11–12 scales above the lateral line and 21–25 gill rakers. Capoeta anamisensis is also distinguished from all other congeners in the Persian Gulf basin by having four fixed, diagnostic nucleotide substitutions in the mtDNA COI barcode region and five fixed, diagnostic nucleotide substitutions in the mtDNA cyt b region. The type of Capoeta barroisi persica is identified as an aberrant individual of C. trutta and is considered as a synonym of that species.